Phospholipid-supplemented diet impacts on growth, blood metrics, reproductive indices, and fatty acid profiles of Pangasianodon hypopthalmus - Donald Torsabo; Benedict Terkula Iber; Nurizzati Idris; Victor Tosin Okomoda; Ivan Chu Chong Koh; Muhammad Yazed Abduh; Noordiyana Mat Noordin; Ambok Bolong Abol-Munafi (Aquaculture Reports, 2023)
This study explores the effects of phospholipid inclusions in the diet of Pangasianodon hypopthalmus young adults on growth and physiological parameters. Commercial diet was subdivided into four groups and top coated using phospholipid (food grade Soy Lecithin) at 0%, 2%, 6%, and 10%, of feed dry weight resulting in an equivalent of 5%, 7.39%, 11.93% and 15.88% total crude lipid levels in the experimental diets. After 90 days of the feeding trials, the phospholipid inclusion at 6% (total crude lipid 11%) significantly improved blood parameters, while inclusion of phospholipid at 10% resulted in a decrease in white blood cells (WBCs) and its associated components, suggesting it may have been above the optimal level required by the fish. Reproductive hormones; 11-ketotestorone and 17β-estradiol that were observed showed an increase in direct proportion following the increase of phospholipid inclusion. Fatty acids composition of the muscle, liver, and gonads show a similar trend with the dominance of C16:0, C18:1n-9, and C18:3n-3 in the tissues. Also, the hierarchy of the fatty acids in the tissues were in the order of SFA > MUFA > PUFA. However, the composition of MUFA decreased with increase in the phospholipid inclusion These findings suggest that dietary phospholipid inclusion can enhance growth and physiological parameters of P. hypopthalmus.